Neonates with epidermolysis bullosa simplex: a case series - Amalia, Fitri; Wistiani, Wistiani; Astuti, Meira Dewi Kusuma; Rahmat, Yosep Ferdinand (Paediatrica Indonesiana, 2025)
Epidermolysis bullosa is a rare and currently incurable inherited disorders characterized by mechanical fragility of affected tissues which can be fatal. We describe two cases of neonatal Epidermolisis bullosa followed in the high risk neonates ward. The first case presented with bulla at one day after birth with amniotic band syndrome and the second case presented with bulla right after birth with neonatal infection. Keyword: epidermolysis bullosa simplex, neonates